A (Cyber)Literature for the 21st Century: Analysis of Digital Intermediality in Dora García’s Performing Work - Calo Blanco, Alba (2025)
Since the birth of the Internet and the emergence of new technologies, the cultural panorama has seen how some traditional forms have adapted to a series of new practices in what we can call cyberculture. This study analyses the different processes of creation and reception of ‘cyberliterature’, using the work of Dora García as a case study. Dora García (Valladolid, 1965), as an interdisciplinary artist, uses performance, audiovisuals, new technologies and collaborative art to achieve audience interactivity. In her works Heartbeat (1999), The Tunnel People (2000) and Todas las historias (2001) she emphasises the role of narrative. The general objectives of this analysis consist of the review and documentation of these corpora and the specific bibliographical exploration of these fields, in order to document the advancement of intermediality and to study the current possibilities in the field of digital creation and cyberliterature. It also seeks to analyse the new modalities of reception by the public and the role they play in these works. To this end, the perspective from which this study is approached is based essentially on disciplines such as comparative literature and intermedial studies.